2021
DOI: 10.24059/olj.v25i3.2853
|View full text |Cite
|
Sign up to set email alerts
|

Student Performance in Online Classes at a Hispanic-Serving Institution: A Study of the Impact of Student Characteristics in Online Learning

Abstract: As online enrollment increases in the United States, it is important to understand the impact of course modality on student outcomes. In particular, there has been limited research on the effect of course enrollment at Hispanic-serving institutions (HSI). The current study evaluated the effect of online course enrollment on student grades and on student withdrawal rates by comparing outcomes in online and face-to-face classes. The main innovation of this study is to use propensity score analysis to control for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It can teach them to think outside the box, become independent in learning, and truly take responsibility for their education (Plas, 2016). Even though there is no significant difference between an online and face-to-face course in student grades (Cottrell, 2020). Still, face-to-face shows credibility in validating and authenticating students' comprehension.…”
Section: Teaching Mathematics In Different Modalitiesmentioning
confidence: 94%
“…It can teach them to think outside the box, become independent in learning, and truly take responsibility for their education (Plas, 2016). Even though there is no significant difference between an online and face-to-face course in student grades (Cottrell, 2020). Still, face-to-face shows credibility in validating and authenticating students' comprehension.…”
Section: Teaching Mathematics In Different Modalitiesmentioning
confidence: 94%
“…The few studies that explore technology within HSIs focus on online courses, particularly the learning environment, student outcomes, and student characteristics and behaviors. For example, Cottrell (2021) found that online students at an HSI had higher withdrawal rates than students who took in-person classes. Other studies have also explored different online tools that can possibly enhance student learning and outcomes at HSIs, including ePortfolios (Callahan et al, 2021, Pan et al, 2015).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Since HSIs are defined based on enrollment and not on specific policies or pedagogical practices, it is logistically difficult to make empirical claims that apply to all HSIs (Fosnacht & Nailos, 2016); however, Bell et al (2021) recently found evidence to suggest that the "digital divide [in student access to technology and internet during COVID-19] may be more prevalent at HSIs than at previously studied institutions" (p. 115). Furthermore, in the academic years just prior to the pandemic, Cottrell (2021) used propensity score matching to compare HSI student outcomes in online and face-to-face courses and found comparable grades but higher withdrawal rates in online classes.…”
Section: Contextualizing Hispanic-serving Institutionsmentioning
confidence: 99%